Increasing the Chemical Variety of Small-Molecule-Based TLR4 Modulators: An Overview - Romerio, Alessio; Peri, Francesco (Frontiers in Immunology, 2020)
Toll-Like Receptor 4 (TLR4) is one of the receptors of innate immunity, it is activated by Pathogen- and Damage-Associated Molecular Patterns (PAMPs and DAMPs), and triggers pro-inflammatory responses which belong to the repertoire of innate immune responses, thus protecting against infectious challenges and boosting adaptive immunity. Mild TLR4 stimulation by non-toxic molecules resembling its natural agonist (lipid A), provided efficient vaccine adjuvants. The non-toxic TLR4 agonist monophosphoryl lipid A (MPLA) has been approved for clinical use, thus suggesting the development of other TLR4 agonists as adjuvants or drugs for cancer immunotherapy. TLR4 excessive activation by Gram-negative bacteria lipopolysaccharide (LPS) leads to sepsis, while TLR4 stimulation by DAMPs is a common mechanism in several inflammatory and autoimmune diseases. TLR4 inhibition by small molecules and antibodies could therefore provide access to innovative therapeutics targeting sepsis, acute and chronic inflammations. The potential use of TLR4 antagonists as anti-inflammatory drugs with unique selectivity and a new mechanism of action compared to corticosteroids or other non-steroid anti-inflammatory drugs, fuelled the search for compounds of natural or synthetic origin able to block or inhibit TLR4 activation and signalling. The wide spectrum of clinical setting to which TLR4 inhibitors can be applied include autoimmune diseases (rheumatoid arthritis, inflammatory bowel diseases), vascular inflammation, neuroinflammations and neurodegenerative diseases. The last advances (from 2017) in TLR4 activation or inhibition by small molecules (molecular weight <2 kDa) are reviewed here. Studies on pre-clinical validation of new chemical entities (drug hits) on cellular or animal models, as well as new clinical studies on previously developed TLR4 modulators are reported. Innovative TLR4 modulators discovered by computer-assisted drug design and artificial intelligence approach are described. Some “old” TLR4 agonists or antagonists such as MPLA or Eritoran are under study for repositioning in different pharmacological contexts. The mechanism of action of the molecules and the level of TLR4 involvement in their biological activity are critically discussed.